2017
DOI: 10.1186/s12911-017-0509-2
|View full text |Cite
|
Sign up to set email alerts
|

Routine health information system utilization and factors associated thereof among health workers at government health institutions in East Gojjam Zone, Northwest Ethiopia

Abstract: BackgroundUsing reliable information from routine health information systems over time is an important aid to improving health outcomes, tackling disparities, enhancing efficiency, and encouraging innovation. In Ethiopia, routine health information utilization for enhancing performance is poor among health workers, especially at the peripheral levels of health facilities. Therefore, this study aimed to assess routine health information system utilization and associated factors among health workers at governmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

21
109
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(144 citation statements)
references
References 21 publications
21
109
13
1
Order By: Relevance
“…This finding was supported by that of a study conducted in East Gojjam zone [24]. This might be due to the attention given by the government to district health facilities in terms of supervision and regular feedback [28, 37].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This finding was supported by that of a study conducted in East Gojjam zone [24]. This might be due to the attention given by the government to district health facilities in terms of supervision and regular feedback [28, 37].…”
Section: Discussionsupporting
confidence: 75%
“…According to our findings, the magnitude of routine health information utilization of health care professionals was 78.5%. This finding is higher than that of a study conducted in North Gondar (22.5%) [22], Jimma (32.9%) [23], East Gojjam (45.8%) [24], Hadiya zone (69%) [25], west Amhara (38%) [29], and in Ethiopia (48%) [2]. This variation might be due to differences in study periods.…”
Section: Discussionmentioning
confidence: 57%
“…This could highly affect the decision-making practices of the Ethiopian health system in terms of resource allocation, planning, service quality and equity. The current data management practice was different from study findings in Southern Ethiopia [16], where 74.3% of HEWs were good in data management. This discrepancy could be due to differences in data management knowledge [limited training], and unclear formats.…”
Section: Discussioncontrasting
confidence: 74%
“…In this study, only 47.4% of the HEWs had good data management knowledge. This clearly indicated that over half of the HEWs practiced data management without knowhow, which leads to poor data and decision quality [11,16,24]. This finding is slightly lower compared to study findings from Southern Ethiopia [16], where 58.2% of HEWs had good data management knowledge.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation